Mechanisms Responsible for Sand Hazards Along Desert Highways and Their Control: A Case Study of the Wuhai–Maqin Highway in the Tengger Desert, Northwest China - An, Zhishan; Zhang, Kecun; Tan, Lihai; Niu, Qinghe; Wang, Tao (Frontiers in Environmental Science, 2022)
Highway in deserts usually suffers from severe sand hazards under the mutual effect of wind-blown sand and the subgrade. In this article, we took the Wuhai-Maqin highway in Tengger Desert, China as an example and revealed the disaster-causing mechanism. Based on the above monitoring results, the sand control system which has six belts has been proposed for high-grade highways in this region, and the sheltering effect was examined through on-site monitoring. The results show that from 2018 to 2019, the drift potential was dominated by northwest, northeast and southerly winds, which belonged to the low energy windy environment, with a compound sand transport direction of southeast. The particle size of surface sediments was mainly distributed between 1.26Φ-2.5Φ, belonging to fine sand and medium sand. The sand flux was mainly concentrated below 30 cm, accounting for 89.46% of the total sand transport. Airflow over the sand control system was significantly attenuated, with a maximum wind speed decrease rate of 95.88%, with average values between 28.85% and 42.65%. The sand blocking efficiency of the sand control system against the near-surface drifting sand flow is more than 90%. This study provides significant reference for the control of highway sand hazards in other areas.